Effect of providing near glasses on productivity among rural Indian tea workers with presbyopia (PROSPER): a randomised trial. Issue 9 (September 2018) - Reddy, Priya Adhisesha; Congdon, Nathan; MacKenzie, Graeme; Gogate, Parikshit; Wen, Qing; Jan, Catherine; Clarke, Mike; Kassalow, Jordan; Gudwin, Ella; O'Neill, Ciaran; Jin, Ling; Tang, Jianjun; et al.
Summary: Background: Presbyopia, age-related decline in near vision, is the most common cause of vision impairment globally, but no trials have assessed its workplace effects. We aimed to study the effect of near glasses on the productivity of tea workers with presbyopia. Methods: This randomised trial was done in tea pickers aged 40 years or older in Assam, India, with unaided near visual acuity (NVA) lower than 6/12 in both eyes, correctable to 6/7·5 with near glasses; unaided distance vision 6/7·5 or greater; and no eye disease. Participants were randomly assigned (1:1) to receive free glasses optimising NVA at working distance (cost including delivery US$10·20 per person), either immediately (intervention group) or at closeout (control group). Participants were stratified by age, sex, and productivity. The primary outcome (investigator-masked) was the difference between groups in the change in mean daily weight of tea picked (productivity), between the 4-week baseline period (June, 2017) and the 11-week evaluation period (July 24, 2017, to Oct 7, 2017). Workers' income was tied to their productivity. Compliance with study glasses was assessed at seven unannounced visits. Results were analysed on an intention-to-treat basis. This trial is registered withClinicalTrials.gov, numberNCT03228199 . Findings: Between July 3, 2017, and July 15, 2017, 1297 (48·1%) of 2699 permanent workers met the age criteria and consented for eye examinations. 751 (57·9%) fulfilled vision criteria and were randomly assigned to the intervention (n=376) or control (n=375) groups. Groups did not differ substantially in baseline characteristics. No participants owned glasses at baseline, 707 (94·1%) received the allocated intervention, and all were followed up and analysed. Between the baseline and evaluation periods, mean productivity in the intervention group increased from 25·0 kg per day to 34·8 kg per day (an increase of 9·84 kg per day), a significantly higher increase than in the control group (from 26·0 kg per day to 30·6 kg per day; an increase of 4·59 kg per day), corresponding to a between-group difference of 5·25 kg per day (95% CI 4·50–5·99; 21·7% relative productivity increase; effect size 1·01 [95% CI 0·86–1·16]; p<0·0001). Intervention-group compliance with study glasses reached 84·5% by closeout. Regression model predictors of greater productivity increase included intervention group membership (5·25 kg per day [95% CI 4·60–5·91], p<0·0001) and, among intervention participants, older age (p=0·039) and better compliance with the intervention (p<0·0001). Interpretation: A substantial productivity increase was achieved in this rural cohort by providing glasses to correct presbyopia, with little cost and high intervention uptake. Funding: Clearly.